Dinamika Keuangan Sosial Islam: Tren Zakat Produktif dan Pembiayaan Syariah Sektor UMKM terhadap Ketimpangan Pendapatan di Indonesia Tahun 2011-2025 - Fitriani, Silmi; cupian, Cupian; Hardiawan, Donny (Universitas Islam Negeri Raden Intan Lampung, 2026)
Income inequality remains a structural challenge in Indonesia’s economic development that has yet to be fully resolved. Islamic social finance instruments, particularly productive zakat and sharia financing for the MSME sector, are believed to play a role in reducing this disparity. This study aims to analyze the trend development of BAZNAS productive zakat and sharia financing for the MSME sector in relation to income inequality, as measured by the Gini Ratio in Indonesia during the period 2011-2025, using quarterly observations where available. The study employs a descriptive quantitative method with trend analysis based on secondary data obtained from BAZNAS financial reports, the Financial Services Authority (OJK), and Statistics Indonesia (BPS). The results show that BAZNAS productive zakat increased significantly from IDR 5.41 billion in 2011 to IDR 149.71 billion in 2025, with a Compound Annual Growth Rate (CAGR) of 26.8%. Meanwhile, sharia financing for the MSME sector increased from IDR 209.85 trillion at the end of 2011 to IDR 305.84 trillion in the first semester of 2025, with a CAGR of 2.84%. At the same time, the Gini Ratio showed a gradual downward trend from 0,410 in March 2011 to 0,375 in March 2025, although it experienced fluctuations due to COVID-19 pandemic during the 2020-2021 period. Descriptive trend analysis identifies a pattern of alignment between the growth of Islamic social finance instruments and the decline in income inequality. The findings indicate that productive zakat expanded at a substantially faster rate than MSME sharia financing, while both instruments displayed a trend broadly aligned with the gradual decline in income equality. However, this relationship cannot yet be directly interpreted as a causal relationship and still requires further empirical investigation.